2019
DOI: 10.1177/1060028019897100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vancomycin Area-Under-the-Curve Dosing Versus Trough Target–Based Dosing in Obese and Nonobese Patients With Methicillin-Resistant Staphylococcus aureus Bacteremia

Abstract: Background: A vancomycin target of area under the curve to minimum inhibitory concentration (AUC:MIC) ratio ≥400 is recommended for treatment of methicillin-resistant Staphylococcus aureus (MRSA) bacteremia. Objective: To evaluate vancomycin total daily dose (TDD) achieving trough targets versus a calculated strategy achieving AUC targets based on body mass index (BMI). Methods: A retrospective cohort study was performed within a large hospital network. Patients with MRSA bacteremia were eligible if they recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…It was also reported that total daily dose of VCM for trough-based dosing (2390.76 ± 1224.59 mg) differed significantly from AUCbased dosing (1985.07 ± 616.18 mg) across the cohort, and these differences were dependent on patients' BMI, although not the short status, but the obese patients showed significant differences of total dose of VCM. 20 These data suggested similar results with our study that the short status looked a significant factor; however, it did not show the significant relation with VCM trough finally. The hematological patients were also not usually obese and did not show high inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…It was also reported that total daily dose of VCM for trough-based dosing (2390.76 ± 1224.59 mg) differed significantly from AUCbased dosing (1985.07 ± 616.18 mg) across the cohort, and these differences were dependent on patients' BMI, although not the short status, but the obese patients showed significant differences of total dose of VCM. 20 These data suggested similar results with our study that the short status looked a significant factor; however, it did not show the significant relation with VCM trough finally. The hematological patients were also not usually obese and did not show high inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have found that pharmacokinetic parameters of vancomycin are associated with the renal function, age, weight, combined medications, and other factors (Chu et al, 2016;Covvey et al, 2019;Yahav et al, 2019). Based on the population pharmacokinetic approach, we can screen out variables that influence the parameters of vancomycin pharmacokinetics, and establish formulas describing individual pharmacokinetic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of obese patients receiving vancomycin, switching to an AUC-based approach reduced total daily doses of vancomycin. 18 Although obese patients exhibited a nearly twofold higher rate of AKI compared with non-obese patients, similar rates of nephrotoxicity were observed in troughbased monitoring approach compared with an AUC-based strategy.…”
Section: Trough-based Versus Area-under-the-curve Therapeutic Drug Mo...mentioning
confidence: 79%